Circular RNA hsa_circ_0003575 regulates oxLDL induced vascular endothelial cells proliferation and angiogenesis - Li, Chen-Ye; Ma, Lan; Yu, Bo (Biomedicine & pharmacotherapy, 2017)
Circular RNAs (circRNAs) are a novel class of RNAs generated from back-splicing and characterized by covalently closed continuous loops. Recently, circRNAs have recently shown large regulation on cardiovascular system, including atherosclerosis. The present study aims to investigate the circRNA expression profile and identify their roles on vascular endothelial cells induced by oxLDL. Human circRNA microarray analysis revealed that total 943 differently expressed circRNAs were screened with 2 fold change. Hsa_circ_0003575 was validated to be significantly up-regulated in oxLDL induced HUVECs. Loss-of-function experiments indicated that hsa_circ_0003575 silencing promoted the proliferation and angiogenesis ability of HUVECs. Bioinformatics online programs predicted the potential circRNA-miRNA-mRNA network for hsa_circ_0003575. In summary, circRNA microarray analysis reveals the expression profiles of HUVECs and verifies the role of hsa_circ_0003575 on HUVECs, providing a therapeutic strategy for vascular endothelial cell injury of atherosclerosis.